Cognitive training for technical and non‐technical skills in robotic surgery: a randomised controlled trial. (12th June 2018) - Raison, Nicholas; Ahmed, Kamran; Abe, Takashige; Brunckhorst, Oliver; Novara, Giacomo; Buffi, Nicolò; McIlhenny, Craig; van der Poel, Henk; van Hemelrijck, Mieke; Gavazzi, Andrea; Dasgupta, Prokar
Abstract : Objective: To investigate the effectiveness of motor imagery (MI) for technical skill and non‐technical skill (NTS) training in minimally invasive surgery (MIS). Subjects and Methods: A single‐blind, parallel‐group randomised controlled trial was conducted at the Vattikuti Institute of Robotic Surgery, King's College London. Novice surgeons were recruited by open invitation in 2015. After basic robotic skills training, participants underwent simple randomisation to either MI training or standard training. All participants completed a robotic urethrovesical anastomosis task within a simulated operating room. In addition to the technical task, participants were required to manage three scripted NTS scenarios. Assessment was performed by five blinded expert surgeons and a NTS expert using validated tools for evaluating technical skills [Global Evaluative Assessment of Robotic Skills (GEARS)] and NTS [Non‐Technical Skills for Surgeons (NOTSS)]. Quality of MI was assessed using a revised Movement Imagery Questionnaire (MIQ). Results: In all, 33 participants underwent MI training and 29 underwent standard training. Interrater reliability was high, Krippendorff's α = 0.85. After MI training, the mean (sd ) GEARS score was significantly higher than after standard training, at 13.1 (3.25) vs 11.4 (2.97) ( P = 0.03). There was no difference in mean NOTSS scores, at 25.8 vs 26.4 ( P = 0.77). MI training was successful with significantly higher imagery scores than standard training (mean MIQ score 5.1 vs 4.5, P = 0.04). Conclusions: Motor imagery is an effective training tool for improving technical skill in MIS even in novice participants. No beneficial effect for NTS was found.